Talking Like a Teacher-A Study of Pre-Service Teachers' Voice and Speech Characteristics in Learning and Teaching Situations - Kati Järvinen; Anna-Leena Kähkönen; Pasi Nieminen; Terhi Mäntylä (MDPI AG, 2024)
Voice and speech are educational tools and a medium of pedagogy for teachers. Teachers tend to modify their voice and speech to support learning. This study aimed to investigate whether pre-service teachers modify their speech and voice in teaching compared to peer learning speech and whether the changes can promote learning and be beneficial for the speakers. Nine pre-service physics teachers' voices were recorded in three learning situations and in one teaching session with similar external circumstances. Duration of speech turns, pausing, speech rate, fundamental frequency (F0) and its variation, sound pressure level (SPL) and its range, and voice quality were analyzed. Results showed that the participants had longer speech turns, decreased speech rate, and increased pausing when teaching compared to speech in peer learning situations. F0 and SPL were higher in teaching, indicating that the teaching situation was more stressful than the peer learning situation. For F0, this was confirmed by correlation analysis. From the learning point, increased pausing and slower speech rate may be beneficial, but increased F0 and SPL may, on the other hand, be harmful to future teachers as they can increase the risk of vocal overloading. Voice training for future teachers is strongly recommended.